Breaks in the cycle: dissolved organic nitrogen in terrestrial ecosystems. Issue 4 (1st May 2003) - Neff, Jason C.; Chapin, F Stuart; Vitousek, Peter M.
Abstract : Dissolved organic nitrogen (DON) is present in soils and streams around the world. We are only now beginning to explore the important roles this chemically heterogeneous mixture of compounds plays in terrestrial nitrogen (N) cycling. Over centuries, DON leaching may represent a significant "leak" of N, which occurs because plants and microbes cannot prevent DON losses, even in times of high N demand. However, in many ecosystems, plants may "short‐circuit" the terrestrial N cycle by direct uptake of amino acid DON without microbial mineralization of organic N to ammonium (NH4 + ). These apparently contradictory roles for DON in N cycling are due to the biological and physical factors that regulate DON loss, and the fact that there are many biochemical forms of organic N in solution. Recognition of these processes complicates the standard conceptual view of terrestrial N cycling. Here we focus on the dual roles of DON as a nutrient‐loss pathway and as an N source for plants.